Pengaruh Job Instability terhadap Kinerja dengan Variabel Mediator Stres Kerja Karyawan Bank di Surabaya - Siti Halimah; Dwiarko Nugrohoseno (Universitas Negeri Surabaya, 2018)
Since 2008 financial crisis, many banking service personnel have not only lost their confidence, but serious day by day. To promote efficiency and have also caused unemployment rates to be more performance, some enterprises have taken the steps of reorganizing their enterprises, merging. and even laying off their employeesto reduces manpower cost Therefore, employment relationship between the staff and organization become more unstable and forecast with dificulty This research purpose are D to determine influence of job instabiliry toward job performance banking services personnel in Surabaya, 2) to determine influence of Job instability toward job stress banking services personnel in Surabaya, 3) to determine influence of job stress toward job performance banking serices personnel in Surabaya. The sample in this study is banking services personnel of bank rating based on assets February 2010 in Surabaya is consisted of 50 respondents. Sample decision used survey method. Data analysis technique used Partial Least Square (PLS) by software SMART PLS and SPSS 13.0 From the results of the analysis note that 1) there is significant influence between Job instability with job performance and has negative influence, 2) there is significant influence between Job instability with job stress and has positive influence, 3) there is significant influence between job stress with job performance and has negative influence